Production design of an amphibious boat / Rabiatul Adawiah Mohd Razalli - Mohd Razalli, Rabiatul Adawiah (2022)
This project is basically about a production design of amphibious boat that has capabilities to go over land and also the water whether designed with wheels or tracks.It is referred as an amphibious boat for its amphibian quality which can move both on land and water.Amphibious boat is a concept of boat that having versatile usage. It can be put forward for the commercialization purpose with respect to various applications like in the field of military and rescue operations.